A Conservative Reformer in Upper Canada: Charles Fothergill, Responsible Government and the “British Party”, 1824‑1840 - Romney, Paul (Historical Papers / Communications historiques, 1984)
AbstractWhig treatments of the politics of early 19th century Upper Canada have tended to treat the reformers as a group unified behind the concept of "responsible government". As Graeme Patterson has pointed out, though, the concept of responsible government, which lay at the heart of much debate during the 1830s and 1840s, had a variety of meanings, ranging from the traditional Baldwinite view of ministerial responsibility for policy to an elected chamber of a sovereign legislature to the much simpler concept cf effective accountability of the colonial administration to imperial authorities. The author explores a distinctive variant upon the theme cf "responsible government" - that posited by the English-born reformer, Charles Fothergill. After a short, and not par- ticularly distinguished, career as a placeman, Fothergill was dismissed in 1826 for his activities in the House of Assembly. After three years in the mainstream cf reform politics, he broke with W.W. Baldwin, John Rolph and their adherents over the meaning cf responsible government, and proclaimed himself a "conservative reformer." Afterthe Rebellion, he became a tribune of the so-called "British Party" - a group of loyal, conservative, middle-class British immigrants who resented the dominance of the Family Compact. Though Fothergill shared the social conservatism which underlay the Bald- winite view of responsible government, he posited a less radical, more legalistic - and, to the author, more logical - alternative to ministerial responsibility.